PHYTOCHEMICAL SCREENING AND ANTIOXIDANT POTENTIAL OF ANACARDIUM OCCIDENTALE, ACHYRANTHES ASPERA, AND AEGLE MARMELOS - BRIJYOG; LALITESHWAR PRATAP SINGH; SUSHIL KUMAR; SHWETA VERMA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Anacardium occidentale, Achyranthes aspera, and Aegle marmelos are the common plants found in North and South India. The present study identifies the active phytochemicals and antioxidant properties in various extracts derived from dried bark, whole aerial parts, and leaves of the above plants. Materials and Methods: Phytochemical screening included extracts of pet ether, hydroalcoholic, and aqueous. The antioxidant activity was determined by measuring total phenolic contents (TPC), 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging activity (RSA), and total flavonoid content (TFC). Results: The phytochemical screening of A. occidentale, A. aspera, and A. marmelos of dried bark, whole aerial parts, and leaves revealed the presence of flavonoids, phenols, tannins, and proteins. It also contains alkaloids and glycosides. Hydroalcoholic extract of A. occidentale, A. aspera, and A. marmelos showed highest TPC 0.125 mg/g, 0.256 mg/g, and 0.254 mg/g, respectively. TFCs 0.094 mg/g, 0.145 mg/g, and 0.121 mg/g and highest DPPH RSA with the half maximal inhibitory concentration of 125 μg/mL, 105.58 μg/mL, and 98.89 μg/mL compare to the standard ascorbic acid of 21.65 μg/mL. Conclusion: This study showed that the hydroalcoholic extract of A. occidentale, A. aspera, and A. marmelos is potential source of natural antioxidants.